Mid-Life – A Time of Crisis or New Possibilities? (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
With age our knowledge, emotions and the way we behave nature. The commonly held view of mid-life crisis is that it is an emotional state of doubt and anxiety in which a person becomes uncomfortable with the realization that life is half over. It is a potentially stressful period as it usually involves reflection and re-evaluation of one's accomplishments. It usually occurs between the age of 35 and 50 and lasts between 3 and 10 years. This paper compares and contrasts what might be taken as Freud's view on middle age, Jung's idea of individuation, Frankl's idea of will to meaning and Rogers' idea of personal growth; ideas that have relevance to middle age. It also reflects on Erikson's and Peck's view of middle age as a stage in the lifespan development. This paper relates the idea of middle life crisis with Yalom's research on meaning in life and Spinelli's idea of owning experience. It argues that middle age should not necessarily be seen as a time of crisis and loss but of growth and new possibilities.